Patients’ perception of the quality of community pharmacy services using the critical incident technique - Kummer, Ingrid; Mudrić, Jovana; Čikarić, Tamara; Tasić, Ljiljana; Milošević Georgiev, Andrijana; Marinković, Valentina (Vojnosanitetski pregled, 2022)
Background/Aim. The Critical Incident Technique (CIT) is a qualitative research method for measuring consumer satisfaction by collecting and analyzing information on participants and their activities. This method allows participants to present their detailed experiences related to a particular service in the way they perceive them. The aim of this study was to examine patients’ perceptions of an incident that occurred in community pharmacies using CIT and determine recommendations for improving the quality of pharmacy services. Methods. A qualitative study using an interview based on the CIT was conducted in three pharmacies in Serbia, on the territory of Kruševac city. The entire course of the interviews was audio-recorded, which provided detailed research. Results. A total of 68 critical incidents were collected and divided into two groups: positive (37) and negative (31), depending on the (dis)satisfaction of patients with the services of pharmacists in community pharmacies. The following thematic clusters of pharmacy services were covered: accessibility of community-based pharmaceutical services, pharmacist behavior, patient counseling, dispensing drugs and/or medical devices, compounding, and pharmacy sales/commercial practice. Conclusion. The results show that the CIT is a useful tool for evaluating and improving pharmaceutical services. Based on the data collected, various aspects of community pharmacy services can be improved, and further research should be carried out.